Immune-Monitoring Disease Activity in Primary Membranous Nephropathy - Cravedi, Paolo; Jarque, Marta; Angeletti, Andrea; Favà, Àlex; Cantarelli, Chiara; Bestard, Oriol (Frontiers in Medicine, 2019)
Primary membranous nephropathy (MN) is a glomerular disease mediated by autoreactive antibodies, being the main cause of nephrotic syndrome among adult patients. While the pathogenesis of MN is still controversial, the detection of autoantibodies against two specific glomerular antigens, phospholipase A2 receptor (PLA2R) and thrombospondin type 1 domain containing 7A (THSD7A), together with the beneficial effect of therapies targeting B cells, have highlighted the main role of autoreactive B cells driving this renal disease. In fact, the detection of particularly PLA2R-specific IgG4 antibodies has resulted in a paradigm shift regarding the diagnosis as well as a better prediction of the progression and recurrence of primary MN. Nevertheless, some patients do not show remission of the nephrotic syndrome or do rapidly recur after immunosuppression withdrawal, regardless the absence of detectable anti-PLA2R antibodies, thus highlighting the need of other immune biomarkers for MN risk-stratification. Notably, the exclusive evaluation of circulating antibodies may significantly underestimate the magnitude of the global humoral memory immune response since it may exclude the role of antigen-specific memory B cells. Therefore, the assessment of PLA2R-specific B-cell immune responses using novel technologies in a functional manner may provide novel insight on the pathogenic mechanisms of B cells triggering MN as well as refine current immune-risk stratification solely based on circulating autoantibodies.